The Faces of Contemporary Labour Market Segmentation - Kryńska, Elżbieta (Olsztyn Economic Journal, 2017)
This article discusses the segments of contemporary labour markets and identifies the causes of evolution and the present-day manifestations and mechanisms of segmentation. To this end, changes occurring in the world today and the progress of research into labour market phenomena over the last 25 years are analysed. The article also provides an insight into the various types of labour market segmentation that underlie its functioning, i.e. competition-driven segmentation, informational segmentation, network-based segmentation and behavioural segmentation. The theoretical underpinning of the article is the concept of a dual labour market made up of a primary market and a secondary market. The analysis offers two main conclusions. Firstly, the labour market segmentation that we observe today causes an expansion of its secondary segment. Secondly, to identify the contemporary face of labour market segmentation, many extensive studies of the institutional, economic, social and psychological aspects of this process are necessary.